Publisher Correction: Clinical activity and molecular correlates of response to atezolizumab alone or in combination with bevacizumab versus sunitinib in renal cell carcinoma. (December 2018) - McDermott, David; Huseni, Mahrukh; Atkins, Michael; Motzer, Robert; Rini, Brian; Escudier, Bernard; Fong, Lawrence; Joseph, Richard; Pal, Sumanta; Reeves, James; Sznol, Mario; Hainsworth, John; et al.
In the version of this article originally published, there was an error in Fig. 2n. The top line of the HR comparison chart originally was Atezo + bev vs sun. It should have been Atezo + bev vs atezo. The error has been corrected in the HTML and PDF versions of this article.